2017
DOI: 10.1016/j.ceramint.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The decrease of depolarization temperature and the improvement of pyroelectric properties by doping Ta in lead-free 0.94Na 0.5 Bi 0.5 TiO 3 -0.06BaTiO 3 ceramics

Abstract: Ta-doped lead-free 0.94NBT-0.06BT-xTa (x = 0.0-1.0 %) ceramics were synthesized by a conventional solid-state route. XRD shows that the compositions are at a morphotropic phase boundary where rhombohedral and tetragonal phases coexist. The depolarization temperature (Td) shifted to lower temperature with the increase of Ta content. The pyroelectric coefficient (p) of doped ceramics greatly enhanced compared with undoped material and reached a maximum of 7.14 x10-4 C.m-2. °C-1 at room temperature (RT) and 146.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In addition, the shows huge enhancement from 55.3 to 740.7 (x10 -4 C.m -2 .°C -1 ) at Td (85°C) for composition NBT-0.06B1.02TiO3 [21]. We also studied the effects of Ta doped in NBT-0.06BT on the pyroelectric properties and reported that the pyroelectric coefficient highly enhanced from 3.14 to 7.14 (x10 -4 C.m -2 .°C -1 ) at RT at Ta=0.2% and the same composition shows the maximum to 146.10 x10 -4 C.m -2 .°C -1 at Td (78.8°C) [22]. Furthermore, our recent investigation of NBT-0.06BT doped with La reveals that the pyroelectric properties of NBT-0.06BT were greatly improved by La doping from 3.14 to 7.42 (x10 -4 C.m -2 .°C -1 ) at RT at La=0.5% and to 105.40 x10 -4 C.m -2 .°C -1 at Td (67.9°C ) at La =0.2% [23].…”
Section: Introductionmentioning
confidence: 92%
“…In addition, the shows huge enhancement from 55.3 to 740.7 (x10 -4 C.m -2 .°C -1 ) at Td (85°C) for composition NBT-0.06B1.02TiO3 [21]. We also studied the effects of Ta doped in NBT-0.06BT on the pyroelectric properties and reported that the pyroelectric coefficient highly enhanced from 3.14 to 7.14 (x10 -4 C.m -2 .°C -1 ) at RT at Ta=0.2% and the same composition shows the maximum to 146.10 x10 -4 C.m -2 .°C -1 at Td (78.8°C) [22]. Furthermore, our recent investigation of NBT-0.06BT doped with La reveals that the pyroelectric properties of NBT-0.06BT were greatly improved by La doping from 3.14 to 7.42 (x10 -4 C.m -2 .°C -1 ) at RT at La=0.5% and to 105.40 x10 -4 C.m -2 .°C -1 at Td (67.9°C ) at La =0.2% [23].…”
Section: Introductionmentioning
confidence: 92%
“…However, their low resistivity and high coercive field hinders the practical application for pyroelectric energy harvesting . Researchers have engaged to improve the pyroelectric coefficient of BNT ceramics by combing the BNT‐based ceramics with another compositions, such as BaTiO 3 (BT), (Bi 0.5 K 0.5 )TiO 3 (BKT), etc., to construct new phase structures . For example, Feifei Guo et al reported that adding Ba(Zr 0.055 Ti 0.945 )O 3 into BNT ceramics to construct the rhombohedral‐tetragonal morphotropic phase boundary (MPB) increased the pyroelectric coefficient to 5.7 × 10 −4 C/m 2 /K at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…23 Moreover, the p of BNT-BT ceramics can be significantly enhanced from 3.15 9 10 À8 to 6.99 9 10 À8 Ccm À2 K À1 through a modulation of Na + /Bi 3+ molar ratio. 24 Doping with elements such as Ba, 25 Mn, 26 and La 27 is another effective way to improve the pyroelectric properties. Recently, a rather high p of 7.42 9 10 À8 Ccm À2 K À1 in BNT-BT ceramics was achieved by Balakt et al through La doping.…”
Section: Introductionmentioning
confidence: 99%